1997
DOI: 10.1159/000461949
|View full text |Cite
|
Sign up to set email alerts
|

Human Parvovirus B19 and Blood Products

Abstract: Background and objectives: Human B19 parvovirus (B19), identified in 1975, was only recognised as the causative agent of fifth disease in 1983. The incidence of viraemia is low, around 1 in 1,000, but is sufficient to ensure that most plasma pools for fractionation contain some virus. While infection usually occurs in childhood and is benign, chronic infection sometimes occurs and may be of concern in certain patient groups. Materials and methods: This review is based on a meeting held in March 1995, and addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 106 publications
3
64
0
3
Order By: Relevance
“…Despite the development and presence of B19-specific immune reactions, ϳ20% of all B19 infections show a prolonged state of viremia or viral persistence restricted to the synovial fluid, and viral genomes are detected in bone marrow or other organs, e.g., synovial tissue, liver, or myocardium, for several years after infection (4,8,12,13,19,27,(29)(30)(31)(32)(33). Compared with our age-matched control group and compared with healthy adult blood donors, who have been shown to contain B19 DNA in 7% and in 0.1% up to 0.6% of cases, respectively (34)(35)(36), viral genomes were detected in 35% of arthritis patients in the present study. In those cases in which DNA sequence analysis after PCR amplification was successful, parvovirus B19 genotype 1 genome sequences with minor nucleotide and amino acid changes were detected.…”
Section: Discussionmentioning
confidence: 83%
“…Despite the development and presence of B19-specific immune reactions, ϳ20% of all B19 infections show a prolonged state of viremia or viral persistence restricted to the synovial fluid, and viral genomes are detected in bone marrow or other organs, e.g., synovial tissue, liver, or myocardium, for several years after infection (4,8,12,13,19,27,(29)(30)(31)(32)(33). Compared with our age-matched control group and compared with healthy adult blood donors, who have been shown to contain B19 DNA in 7% and in 0.1% up to 0.6% of cases, respectively (34)(35)(36), viral genomes were detected in 35% of arthritis patients in the present study. In those cases in which DNA sequence analysis after PCR amplification was successful, parvovirus B19 genotype 1 genome sequences with minor nucleotide and amino acid changes were detected.…”
Section: Discussionmentioning
confidence: 83%
“…Consequently, B19 contamination of pooled blood products is of major significance, primarily due to the high physicochemical tolerance of B19 to many of the treatments used in plasma processing allied to the extremely high levels of viremia in acutely infected, and often asymptomatic, individuals (Ͼ10 12 genome equivalents/ml) (15). These factors combine to present significant challenges to manufacturers in terms of the production of B19-free material.…”
mentioning
confidence: 99%
“…Nonetheless, the availability of these methods-combined with reliable methods for antibody detection and the introduction of international-standard preparations for the quantitation of B19 immunoglobulin G (IgG) and, more recently, B19 DNA-is leading to further improvements in the situation in which manufacturers had depended on the presence of high levels of B19 IgG alone, in pooled plasma products, as an indicator of product safety (9,13,15,17). Furthermore, a recent report has shown that 1 IU of B19 DNA equals 0.65 genome equivalent (1).…”
mentioning
confidence: 99%
“…MF is the process of removing contaminants in the 0.025 to 10.0 µm range from fluids by passage through a microporous medium, such as a membrane filter. On the other hand, NF involves the filtration of minute particles using a membrane filter with extremely small 30 pores and is especially effective in the removal of non-enveloped viruses that are resistant to inactivation methods such as heat or solvent/detergent treatments [13][14][15][16][17]. The NF method uses a pressure driven separation process, with electrolyte selectivity dependent on the pore size provided by the membrane structure and the membrane pore potential characteristics.…”
Section: Filtration Of Virusesmentioning
confidence: 99%